7 - 1.LEE, Eddy (Ed.) - Export-Led Industrialization and Development (ILO - Asian Employment Programme, Bangkok 1981). / 2. FROBEL, F.; HEINRICHS, J. and KREYE, O. - The New Inter- national Division of Labour (Cambridge University Press, 1980) - Mkandawire, Thandika (Africa Development, 1984)
Thandika MKANDAWIRE, CODESRIA , Dakar - Senegal